Kadar Interleukin 10 (IL-10) Malaria dan Anemia - Mande, I Nyoman (Airlangga University Press, 2011)
Anaemia is an important complication of malaria, and its pathogenesis is not well understood. High level of the Th2 cytokine (such as IL-10), which counteract the Th1 cytokine, might prevent the development of severe malarial anaemia. The purpose of this study was to know the comparation between the plasma level of IL-10 in malaria falciparum patients with anaemia and without anaemia. The plasma level of IL-10 was examined in 16 malaria falciparum patients with anaemia and 16 malaria caused by P. falciparum patients without anaemia samples taken from patients at the primary health centres in West Lombok and Centre Lombok during March until July 2008. The samples were measured using ELISA. The concentration of haemoglobin (Hb) was measured using hematological analyzer. The anaemia concentration of Hb is < 11 g/dL. The results were analyzed using two (2) sample t test with SPSS ver.13.The plasma level of IL-10 in malaria patients caused by P. falciparum with anaemia was 8.81(3.04) [mean(SD)] pg/mL where as the plasma level of IL-10 in malaria falciparum patients without anaemia was 47.99(25.26) pg/mL. The mean of IL-10 level in malaria falciparum patients with anaemia was significantly lower than that of malaria patients caused by P. falciparum without anaemia (p=0.000). Anemia merupakan salah satu komplikasi yang penting di malaria, dan patogenesisnya di penyakit tersebut belum sepenuhnya difahami. Kadar sitokin Th2 (seperti IL-10) yang tinggi, dan menetralkan sitokin Th1, mungkin dapat mencegah perkembangan anemia di pasien malaria yang lebih berat. Tujuan penelitian ini adalah untuk mengetahui kadar IL-10 plasma dengan membandingkan yang terdapat di antara penderita malaria dengan anemia dan tanpa anemia. Kadar IL-10 plasma di 16 pasien malaria penyebab P. falciparum yang beranemia dan 16 pasien malaria penyebab P. falciparum tanpa anemia yang berasal dari Puskesmas Lombok Barat dan Lombok Tengah selama bulan Maret sampai Juli 2008, diukur dengan menggunakan cara ELISA. Kadar hemoglobin (Hb) diukur dengan menggunakan alat hematology analyzer. Anemia adalah kepekatan Hb <11 g /dL. Hasil telitian dianalisis menggunakan uji statistik t dua sampel bebas dengan SPSS ver.13. Kadar rerata IL-10 plasma di pasien malaria penyebab P. falciparum beranemia adalah 8,81 ± 3,04 pg/mL sedangkan kadar rerata IL-10 plasma di pasien malaria penyebab P. falciparum tanpa anemia adalah 47,99 ± 25,26 pg / mL. Rerata kadar IL-10 plasma di pasien malaria beranemia secara berarti lebih rendah daripada rerata kadar IL-10 plasma pada penderita malaria tanpa anemia (p = 0,000).